Dolutegravir plus lamivudine for the treatment of HIV-1 infection. Issue 4 (2nd April 2020) - Ciccullo, Arturo; Baldin, Gianmaria; Borghetti, Alberto; Di Giambenedetto, Simona
ABSTRACT: Introduction : Recent data on the 2-drug regimen (2DR) with dolutegravir (DTG) plus lamivudine (3TC) have shown high efficacy and tolerability both in treatment-naïve and experienced HIV-positive patients. Current guidelines recommend DTG+3TC as an alternative to triple antiretroviral therapy (ART) in selected patients to reduce long-term toxicity and costs. Areas covered : This review is intended to provide insight about the efficacy, safety, and tolerability of a 2DR with DTG+3TC in naïve and treatment-experienced patients. Expert opinion : Data from clinical trials and from real-life show that DTG+3TC is an effective and safe switch option for the treatment of experienced patients. In treatment-naïve patients, DTG+3TC has shown non-inferiority compared to standard 3-drug regimens but is less effective in severely immunocompromised naïve patients (i.e. with a CD4+ cell count below 200 cell/mm3); furthermore, current guidelines have upgraded this dual regimen to recommended first-line strategy, but indicate that it should not be used without genotypic resistance results. Moreover, this regimen is not feasible for HBV-coinfected individuals and should not be used during pregnancy. Currently, out of 2-drug regimens, DTG+3TC is one of clinicians' preferred option as it requires no pharmacokinetic booster, has a low risk of drug interaction, and does not require food intake.